Exploring the use and quality of Internet discussion forums in pregnancy: A qualitative analysis. Issue 1 (4th October 2019) - Ellis, Leila; Roberts, Lesley
Abstract: Background: The Internet is widely used as a source of health information to assist decision making in pregnancy. Concerningly, the quality of information shared on online pregnancy forums is unclear. Our objectives were to explore online pregnancy forum health‐related use and evaluate quality of information shared. Methods: This retrospective qualitative study had two phases of data collection and analysis. First, thematic analysis of a representative sample (n = 480) of posts explored motivators for forum use. Second, a subgroup (n = 153) of threads with clinical content was assessed for congruence with reputable sources. Results: Common motivators for forum engagement were a desire for lived experience, unlimited access, and the opportunity to express emotions. Of 1098 responses sharing advice, information, or experience, 601 (54.7%) were accurate; 230 (20.9%) were erroneous, incomplete, or misleading; and 267 (24.3%) lacked credible evidence. Of these, 60 (5.5%) were potentially harmful. Responses often directed women to a health care practitioner, but concerningly, failed to refer ten women in need of urgent medical assessment. Few discussions were self‐regulating, with only 12 of 230 (5.2%) poor‐quality messages subsequently rectified. Conclusions: Exchange of information and emotional support among peers are key functions of online pregnancy forums. There is a modest prevalence of poor‐quality or potentially harmful information but more concerningly a lack of peer moderation. We suggest health care practitioners ensure pregnant women have a clear understanding of when clinical consultation is required. Clinicians may wish to discuss the supportive community aspects of online forums in cases where offline support is lacking.